The First Online Capillary Electrophoresis-Microscale Thermophoresis (CE-MST) Method for the Analysis of Dynamic Equilibria—The Determination of the Acidity Constant of Fluorescein Isothiocyanate - Paweł Mateusz Nowak; Maria Klag; Gabriela Kózka; Małgorzata Gołąb; Michał Woźniakiewicz (Molecules, 2022)
This article presents the first successful application of a capillary electrophoresis-microscale thermophoresis tandem technique (CE-MST) for determining the values of equilibrium constant, realized by connecting online the CE and MST instruments using a fused-silica capillary. The acid-base dissociation of fluorescein isothiocyanate, expressed by the acidity constant value (pKa), was used as a model. The measurement procedure consisted of introducing a mixture containing the analyte and a deliberately added interferent into the CE capillary, electrophoretic separation of the analyte from the interferent, the detection of the analyte with a CE-integrated detector, detection with a MST detector, and then stopping the flow temporarily by turning off the voltage source to conduct the thermophoretic measurement. The analysis of migration times, peak areas and MST responses obtained concurrently for the same sample allowed us to determine the pKa value using three independent methods integrated within one instrumentation. The analyte was effectively separated from the interferent, and the acidity values turned out to be consistent with each other. An attempt was also made to replace the standard commercial CE instrument with a home-made portable CE setup. As a result, the similar pKa value was obtained, at the same time proving the possibility of increasing cost efficiency and reducing energy consumption. Overall, the CE-MST technique has a number of limitations, but its unique analytical capabilities may be beneficial for some applications, especially when sample separation is needed prior to the thermophoretic measurement.